Cáncer de mama, diagnóstico mediante marcadores tumorales. - Carmilema Tuquinga, María Fernanda (2024)
The main objective of this research study was to investigate breast cancer which is the most frequent neoplasm and the most common cause of death in women worldwide. Using a bibliohemerographic review, the different types of tumor markers used in its diagnosis, as well as the epidemiological and clinical characteristics and the most frequent histological types of breast cancer. The research was carried out with a qualitative approach, a descriptive level, a non-experimental bibliographic documentary design, and cross-sectional and the technique applied was mainly observation. A total of 62 scientific articles were finally reviewed after applying the inclusion and exclusion criteria. The information was obtained through an exhaustive search in different databases such as Pubmed, Medigraphic, Scielo, ResearchGate, Elsevier, Google Scholar, Dialnet, Redalyc, and Solca Library. The results show that malignant breast neoplasia is more frequent in women aged 40-60 years with a family history of breast cancer and late menopause. In addition, smoking, alcohol intake, and a low level of education are prevalent. The main clinical manifestations reported by various researchers were the presence of a lump, nipple discharge, and breast pain. The most frequent histological type was invasive ductal carcinoma. The most commonly used and recommended tumor markers are CA 15-3 and CEA. In addition, the most widely used method was electrochemiluminescence immunoassay due to its high sensitivity and specificity, which improves diagnostic accuracy.